Financial Distress Analysis: Cigarette Companies on Idx, Pandemic & Excise Tax Impact (2019-2023) - Ifan Muhamad Lutfan; Lela Nurlela Wati; Agus Zainul Arifin (Journal of Management Economic and Financial, 2025)
The policy of increasing tobacco excise taxes, implemented gradually in recent years, has created challenges for companies. Since 2019, various challenges have emerged, especially due to the COVID-19 pandemic that affected the whole world and the government's policy of increasing tobacco excise taxes. This study aims to analyze the condition of financial distress in cigarette companies listed on the Indonesia Stock Exchange during the period 2019 to 2023, as well as identify the influence of external factors in the form of an increase in excise rates and the COVID-19 pandemic on the level of distress risk. This research method is quantitative with a descriptive and associative approach. The research sample consisted of four cigarette companies, namely PT HM Sampoerna Tbk (HMSP), PT Gudang Garam Tbk (GGRM), PT Wismilak Inti Makmur Tbk (WIIM), and PT Bentoel Internasional Investama Tbk (RMBA). The results showed that HMSP and WIIM were consistently in a healthy financial condition according to all three models, while GGRM was volatile but relatively stable. In contrast, RMBA shows a score that indicates a distressed condition almost every year. The study concludes that external factors have a significant contribution to the risk of bankruptcy of cigarette companies. Predictive models can be used as an early detection tool against declining corporate financial health.